Developing a system to improve food distribution in public schools: a case in Mogi das Cruzes - Maiellaro, João Roberto; Reis, João Gilberto Mendes dos; Muçouçah, Fernando Juabre; Santos, Daniel Nery dos (Agrarian, 2019)
School feeding programs are present in different countries. These programs promote healthy food by purchasing food directly from local food producers, based on familiar agriculture. This paper studied a food supply chain of the school feeding in Mogi das Cruzes city, one of the most important food producer cities in Brazil. The local producers supply food for schools through the National School Food Program (PNAE). Data were availabled by the secretaria da agricultura. Using the locations of the schools and food producers, a spatial analysis of the supply network was conducted in a geographic information system. At last it was possible to conclude that a new distribution point can bring relevant improvements to the logistics operation.